Note the equal sign. What you do to one side, you do to the other.
Isolate the variable. Divide 4 from both sides
(-52)/4 = (4m)/4
m = -52/4
m = -13
-13 is your answer for m
hope this helps
Answer:
(2 x +1) ( x + 1) = 2 x² + 3 x + 1
Step-by-step explanation:
The steops used to find the product of (2 x + 1) (x + 1) are
=( 2 x )× x + (2 x) × 1 + x + 1
= 2 x² + 2 x + x + 1
= 2 x² + 3 x + 1
Answer:
let R represent red hair
let G represent green eyes
<em>from</em><em> </em><em>Baye's</em><em> </em><em>theorem</em><em>:</em>
<em>
</em>
P(RnG) = 5
![P(G) = { \sum}(green \: hair) \\ = (3 + 5 + 5) \\ = 13](https://tex.z-dn.net/?f=P%28G%29%20%3D%20%7B%20%5Csum%7D%28green%20%5C%3A%20hair%29%20%5C%5C%20%20%3D%20%283%20%2B%205%20%2B%205%29%20%5C%5C%20%20%3D%2013)
Therefore:
![P( \frac{R}{G} ) = \frac{5}{13} \\ = 0.385](https://tex.z-dn.net/?f=P%28%20%5Cfrac%7BR%7D%7BG%7D%20%29%20%3D%20%20%5Cfrac%7B5%7D%7B13%7D%20%20%5C%5C%20%20%3D%200.385)
The conditional relative frequency = 0.385
Answer:
Step-by-step explanation:
The triangles are congruent when corresponding sides are congruent.
__
ΔFGH ≅ ΔABC means corresponding sides are ...
(GH, BC) = (V, 16)
(HF, CA) = (48, W)
Corresponding sides being congruent means ...
V = 16
W = 48